2011
DOI: 10.1111/j.1524-4741.2011.01089.x
|View full text |Cite
|
Sign up to set email alerts
|

Current Overview of the Management of Urogenital Atrophy in Women with Breast Cancer

Abstract: Systemic treatments for women with breast cancer frequently induce urogenital symptoms that can negatively impact a women's quality of life. Urogenital atrophy is frequently undiagnosed and untreated, particularly in breast cancer survivors. Symptoms of urogenital atrophy can usually be relieved with vaginal estrogen preparations, but risk of recurrence and safety is undefined in women with a history of breast cancer. Treatment with nonhormonal modalities including vaginal moisturizers or lubricants and lifest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 41 publications
0
31
0
2
Order By: Relevance
“…A review of various vaginal and oral estrogen agents demonstrated that when they were administered vaginally either as a tablet or ring, the serum estradiol concentration was substantially less than with oral or transdermal estrogen medications. 16 Compared with oral estrogen therapy, consideration of local low-dose vaginal estrogen (eg, vaginal tablet once a week) is reasonable for treatment of severe symptoms, given the potential for much lower serum estradiol concentrations. A clinical trial evaluating the safety of vaginal estrogen preparations is under way (http://clinicaltrials.gov/ ct2/show/NCT00984399).…”
Section: Discussionmentioning
confidence: 99%
“…A review of various vaginal and oral estrogen agents demonstrated that when they were administered vaginally either as a tablet or ring, the serum estradiol concentration was substantially less than with oral or transdermal estrogen medications. 16 Compared with oral estrogen therapy, consideration of local low-dose vaginal estrogen (eg, vaginal tablet once a week) is reasonable for treatment of severe symptoms, given the potential for much lower serum estradiol concentrations. A clinical trial evaluating the safety of vaginal estrogen preparations is under way (http://clinicaltrials.gov/ ct2/show/NCT00984399).…”
Section: Discussionmentioning
confidence: 99%
“…Newer evidence has demonstrated that serum pharmacokinetics can be used to determine the maximum annual dose delivered and serum estradiol levels of various LVETs. Vaginal estrogen tablets (10 mg) prescribed twice a week demonstrated the lowest annual delivered systemic dose as compared to other LVET [44] . Providers should be aware of barriers to breast cancer treatment adherence and take into account individual patient's symptom severity, preference, and potential cancer recurrence risk when considering LVET.…”
Section: Sexual Health Concerns In the Breast Cancer Survivormentioning
confidence: 93%
“…In women with VVA, meticulous vulvar care is important, and products with perfumes or dyes should be avoided (toilet tissue, soaps, fabric softeners, stimulating lubricants, vaginal hygiene products) [44] . Vaginal moisturizers can be used on a regular basis to replace vaginal moisture, whereas lubricants are needed with sexual activity to reduce friction [45] .…”
Section: Management Of Vulvovaginal Atrophy In the Breast Cancer Survmentioning
confidence: 99%
“…However, it is absorbed systemically to some extent and has been shown to increase serum estradiol levels to variable degrees [86,87]. This raises some concerns about the safety of vaginal estrogens in patients with breast cancer, particularly in patients on AI though the clinical implications of this increase in estrogen on breast cancer outcomes is unclear [82,86].…”
Section: Vulvovaginal Symptomsmentioning
confidence: 98%
“…Some suggest that vaginal estrogen therapy can be considered after a discussion of risks and benefits with the patient, particularly as vaginal symptoms that are not well controlled can potentially result in non-compliance or early discontinuation [59]. If utilized, consideration of vaginal estrogens with lower levels of systemic estrogen uptake should be considered [87]. Tamoxifen is associated with less vulvovaginal atrophy and dryness due to its weak pro-agonistic effect on the vagina and changing from an AI to tamoxifen is also a reasonable alternative strategy.…”
Section: Vulvovaginal Symptomsmentioning
confidence: 99%